(untitled) (LACCEI, 2024)
Pesticides are highly toxic chemical compounds used to control pests (insects, weeds, fungi, among others) and diseases that attack crops. In addition, they are potentially dangerous for humans and can have an acute or chronic impact on health depending on the amount and channels of exposure. The present investigation was based on the implementation of the electronic nose and tongue multisensory systems as instruments capable of detecting the presence of pesticides in fruits, because they have been implemented in different fields of the industry as devices capable of classifying and discriminating different contaminants or assess the quality of food. The fruits used in this study were plum, strawberry, apple and cape gooseberry which were contaminated with different pesticides such as: Amistar, Funlate, Across, Bricol, Curzate, Daconil and Preza respectively. For this, solutions with a concentration of 10 ppm of the pesticides were prepared, which were applied to the fruit by means of aspersion in the case of the electronic nose, in terms of the electronic tongue, it became necessary first to macerate the fruit and obtain an extract to add the solution.